Regulation of Nutrient Uptake by Plants 2015
DOI: 10.1007/978-81-322-2334-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Heavy Metals

Abstract: Heavy metals and metalloids are often taken up in toxic concentrations by plants from contaminated soils rich in these constituents. Higher plants have built-in cellular mechanisms for metal detoxification and tolerance which try to save them from such toxicities. An elaborate membrane transport system regulates movement of metal ions across plasma membrane of root cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 202 publications
(188 reference statements)
0
1
0
Order By: Relevance
“…Chamba et al [ 42 ] reported for M. zamorensis BCF (Pb: 0.24–0.59 and Cd: <0.06–1.01) and TF (Pb: 0.17–0.19 and Cd: <0.05–0.29) values, similar TF > 0.1 for Cd in the four treatments, similar TF for Pb at T2, and similar BCF (1.01) to T1 for Cd. Demonstrating that the accumulation and translocation capacity of these metals are presented in different proportions, depending on the concentration and bioavailability of metals, physicochemical characteristics of the soil such as pH and OM content, in addition to the cellular mechanisms of plants to avoid or tolerate the absorption of metals [ 113 , 127 , 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chamba et al [ 42 ] reported for M. zamorensis BCF (Pb: 0.24–0.59 and Cd: <0.06–1.01) and TF (Pb: 0.17–0.19 and Cd: <0.05–0.29) values, similar TF > 0.1 for Cd in the four treatments, similar TF for Pb at T2, and similar BCF (1.01) to T1 for Cd. Demonstrating that the accumulation and translocation capacity of these metals are presented in different proportions, depending on the concentration and bioavailability of metals, physicochemical characteristics of the soil such as pH and OM content, in addition to the cellular mechanisms of plants to avoid or tolerate the absorption of metals [ 113 , 127 , 128 ].…”
Section: Resultsmentioning
confidence: 99%